2020
DOI: 10.3390/pharmaceutics12090836
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Non-Viral Gene Therapy for Treatment of Retinal Degeneration

Abstract: Dysregulation of iron metabolism is observed in animal models of retinitis pigmentosa (RP) and in patients with age-related macular degeneration (AMD), possibly contributing to oxidative damage of the retina. Transferrin (TF), an endogenous iron chelator, was proposed as a therapeutic candidate. Here, the efficacy of TF non-viral gene therapy based on the electrotransfection of pEYS611, a plasmid encoding human TF, into the ciliary muscle was evaluated in several rat models of retinal degeneration. pEYS611 adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Plasmid DNA on the other hand can be delivered to cells in the anterior segment of the eye using physical methods such as current, laser, light, ultrasound, guns, or chemical methods, but it still needs to bypass the corneal barriers [ 40 ]. Naked plasmid DNA, injected in the ciliary muscle, has been efficiently transduced in ciliary muscle cells using a disposable electrotransfer device, allowing the sustained intraocular production of therapeutic proteins in the ocular media for more than 6 months [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Description Of Ocular Barriersmentioning
confidence: 99%
“…Plasmid DNA on the other hand can be delivered to cells in the anterior segment of the eye using physical methods such as current, laser, light, ultrasound, guns, or chemical methods, but it still needs to bypass the corneal barriers [ 40 ]. Naked plasmid DNA, injected in the ciliary muscle, has been efficiently transduced in ciliary muscle cells using a disposable electrotransfer device, allowing the sustained intraocular production of therapeutic proteins in the ocular media for more than 6 months [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Description Of Ocular Barriersmentioning
confidence: 99%
“…Human transferrin electrotransfection in rodents was shown to protect retinal structure and function, reducing microglial infiltration and preserving the integrity of the outer retinal barrier in a photo-oxidative model. Transferrin, a natural iron chelator, delayed also the retina degeneration and decreased oxidative stress [ 119 ]. This work validates iron overload as a therapeutic target for pathologies as retinitis pigmentosa or age-related macular degeneration.…”
Section: Sideroflexins In Aging: May Sfxn Regulate Neuronal Physiomentioning
confidence: 99%
“…The degradation of transferrin results in the liberation of iron ions which accumulate in debris zone. This triggers oxidative stress [75], which contributes to the apoptotis of photoreceptors [69,76]. Intravitreal injections or non-viral delivery of transferrin in its iron-free form (apotransferrin) to chelate unbound iron, or antioxidant biomolecules, delay retinal degeneration in RCS rats, supporting the consistency of such a scenario [75][76][77].…”
Section: Ablation Of Phagocytic Activity By Resident Non-professional Phagocytes Causes Blindness In the Retina And Compromised Fertilitymentioning
confidence: 99%
“…This triggers oxidative stress [75], which contributes to the apoptotis of photoreceptors [69,76]. Intravitreal injections or non-viral delivery of transferrin in its iron-free form (apotransferrin) to chelate unbound iron, or antioxidant biomolecules, delay retinal degeneration in RCS rats, supporting the consistency of such a scenario [75][76][77]. In 2000, two independent research groups concurrently identified a single gene defect, the Mer tyrosine kinase (Mertk) [78][79][80].…”
Section: Ablation Of Phagocytic Activity By Resident Non-professional Phagocytes Causes Blindness In the Retina And Compromised Fertilitymentioning
confidence: 99%